Improving connectivity via multi-user scheduling in 5G and beyond networks - Salman, Hanadi; Janjua, Muhammad Bilal; Arslan, Hüseyin (IEEE - Institute of Electrical and Electronics Engineers, Inc, 2021)
In this paper, a novel, yet efficient, multi-user scheduling scheme based on mode selection and power allocation is presented for 5G and beyond networks. The proposed scheme schedules the users in co-existence (CE) and non coexistence (NCE) modes to maximize the connectivity under signal separability and reliability constraints. In addition, two multi-user scheduling mechanisms; check requirements before scheduling (CRBS) and check requirements after scheduling (CRAS), are proposed for practical scenarios to study the impact of quality of service (QoS) on multi-user scheduling in terms of users' reliability requirements. Analytical results show that CRBS outperforms CRAS and orthogonal multiple access (OMA) schemes in terms of connectivity and system throughput with a complexity trade-off.
Keywords: Connectivity; Reliability; Signal Separability; 5G; Co-Existence; Multi-User Scheduling